(3GdJQHjI GdGYdGejI hOhQ Yde GdfaS GdSjHQGfjs - (3YOfGf SYO(B, (3GdRYHjs ((3YeGf(B:s (3OGQ hGFd ddfTQ(B,s, 2022)
(3cJGH (B"(3GdJQHjI GdEYdGejI hOhQ Yde GdfaS GdSjHQGfj(B" (3jbOe OQGSI TGedI Mhd CgejI GdJQHjI GdEYdGejI aj GdYUQ GdQbej, eY GdJQcjR Ydi GdOhQ GdeMhQj dYde GdfaS GdSjHQGfj aj age Sdhc GdeSJNOejf hJaGYdge eY GdhSGFW GdeNJdaI(B. (3jHOC GdcJGH HJbOje EWGQ JegjOj YGe ddehVhY, Ke jfJbd Edi JMdjd GdEWGQ GdfXQj ddGJUGd hGdEYdGe, eY GdJQcjR Ydi GdJWhQGJ GdMOjKI aj gPG GdeLGd(B. (3HYO Pdc, jJfGhd GdcJGH OQGSI MGdI Yf GdJQHjI GdEYdGejI aj GdCQOf, dJSdjW GdVhA Ydi GdJMOjGJ hGdaQU aj gPG GdSjGb GdeMdj(B. (3hjgJe GdaUd GdQGHY HGdJYQja HGdEYdGe GdLOjO GdQbej hBKGQg Ydi GdaQO hGdeLJeY(B. (3hCNjkQG, jNJJe GdcJGH HJbOje EWGQ efgLj ddHMK aj eLGd GdJQHjI GdEYdGejI, eeG jhaQ COhGJ hCSGdjH ddHGMKjf hGdeeGQSjf aj gPG GdMbd(B.s
(3GdeQGLY U(B.259s
Keywords: (3GdEYdGe (B- (3Yde GdfaS GdSjHQGfjs; (3Yde GdfaS GdSjHQGfjs